Aural foreign bodies and their management: our experience - Harini, Padma; Kudamala, Suneel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Aural foreign bodies (FB) are a common presentation at ENT outpatient department mostly seen in paediatric population. Some are easily managed while others should be dealt with caution and extreme care. The objectives of the study were to analyze the types of aural FB, their incidence in different age groups and evaluate management methods. Methods: This is a prospective descriptive study on patients of all age groups with aural FB presenting to the ENT Outpatient Department in a tertiary care centre for a period of 1 year. The clinical presentation, type of FB, incidence in different age groups and management methods were analyzed. Results: 200 patients aged 2-78 years were evaluated. Age group of under 15 years was most affected (70%). Male to female ratio was 1:1.326. Majority (104 out of 200) presented with a history of FB insertion in the ear while others presented with aural pain and discharge. In 10 cases, ear foreign body was an incidental finding. Most common FB was seeds in children and cotton buds, bird feathers in adults. Most of the cases were managed without anaesthesia with use of headlight. Ear probes were used in 45% cases followed by forceps, suction and syringing in remainder. Conclusions: Most of the aural foreign bodies can be managed in the outpatient department itself without any anaesthesia under direct vision of headlight with the help of simple instruments without any complications.